Probiotic Enterococcus mundtii H81 inhibits the NF-κB signaling pathway to ameliorate Staphylococcus aureus-induced mastitis in mice. (March 2022) - Qiu, Min; Feng, Lianjun; Yu, Zhongxian; Zhao, Caijun; Gao, Siyuan; Bao, Lijuan; Zhang, Naisheng; Fu, Yunhe; Hu, Xiaoyu
Abstract: Mastitis is part of the aggressive diseases that affecting the development of dairy farming. Lactic acid bacteria (LAB), an important microbiological agent of gastrointestinal flora, can effectively promote the development of the immune system. Herein, the objectives of this study is to explore the protective role of LAB on Staphylococcus aureus ( S. aureus )-induced mastitis in mice. 88 strains of suspected LAB were isolated from the milk of healthy dairy cows. Antibacterial activity was screened, and the 16S rRNA sequence analysis showed that the bacteria were Enterococcus mundtii H81 ( E. mundtii H81). Furthermore, the model of mastitis has been established by nipple duct injection of S. aureus in mice, while E. mundtii H81 was treated 2 h before S. aureus injection. Twenty-four hours later of S. aureus infection, the mammary gland tissues were collected. The pathological changes of the mammary gland were observed by H&E staining. The levels of TNF-α and IL-1β were measured by ELISA and the myeloperoxidase (MPO) activity was measured by the MPO assay kit. We also observed the changes of nuclear transcription factor kappa B (NF-κB) by using western blotting. The results showed that E. mundtii H81 pretreatment reduced neutrophil infiltration, and significantly reduce the secretion of TNF-α and IL-1β, down-regulate the phosphorylation of p65 NF-κB and IκB, and the expression of tight junction protein Claudin 3 and ZO-1 was up-regulated. Collectively, our findings showed that E. mundtii H81 protects mammary gland from S. aureus -induced mastitis, which may be a candidate of treatment for mastitis infected by S. aureus . Highlights: Enterococcus mundtii H81 can inhibit the growth of S. aureus. The mechanism of action is to inhibit of NF-KB activation. Enterococcus mundtii H81 protects the integrity of the mammary gland epithelial barrier.